Not all about the buzz: licking, a new foraging behavior of bees in tomato flowers - Bartelli, Bruno Ferreira; Guimarães, Bárbara Matos da Cunha; Borges, Nicole Cristina Machado; Nogueira-Ferreira, Fernanda Helena (Journal of apicultural research, 2024)
Bees that visit flowers of open tomato crops were identified, their pollen collection behavior in the flowers was analyzed, and a new behavior was described. It was evaluated whether improved fruit quality results from additional pollination performed by bees and whether Paratrigona lineata (Lepeletier, 1836) and Apis mellifera L., 1758 are effective pollinators of tomatoes. The pollination experiments in the study were carried out on 2 commercial tomato fields located in the Triângulo Mineiro region (Southeastern Brazil). During the study, the licking was observed and described, a new bee behavior to collect pollen that results in fruit formation. A total of 1036 bees belonging to 14 species were sampled. Paratrigona lineata was the most abundant species (63%), followed by A. mellifera (26%) and Exomalopsis spp. (7%). The other species together accounted for the remaining 4%. In general, additional pollination performed by bees in flowers free for visitation (control group) generated fruits that were larger and heavier, with more seeds. Fruits originating from flowers of the single visit tests with P. lineata and A. mellifera showed, respectively, 30.4% and 20.9% more seeds when compared to tomatoes from bee exclusion treatments. Our results reinforce the importance of pollination services provided by bees in tomato crops and provide evidence that species that do not perform buzz pollination, such as P. lineata and A. mellifera, do act as pollinators of this crop.